Evaluatıon of Restoratıon and Revıtalısatıon Opportunıtıes of Hıstorıcal Industrıal Herıtage in Protected Area of Bilecik-Sögüt (Türkiye) - SEDES, Fatma; IRDEN, Ayhanberk (Architecture Image Studies, 2023)
The concept of protection has lasted since Ottoman Empire Period and the interest belonged to this concept started with the discoveries of the archeological areas in 19th Century. The rich historical heritage at each district of Turkey includes wide range of timeframe from pre-historical periods to now. The excess type and amount of cultural assets urge all the pieces in this field are needed to be filed, protected and saved. The theme of the research is; to give information about the recent situation of factory structures in Bilecik – Söğüt region on the basis of protection sense and to form completeness by refunctioning with the urban fabric. In other word, the goal is; how the archeological heritage areas can be integrated into the inventories of Turkey with the properties and recommendations decided by predicating on universal definitions. On this thesis study, the region where the factory buildings exist in Bilecik – Söğüt protection area is reviewed. The locations, identities and architectural features of factory structures in the region are elaborated. After the evaluation of the recent situation of structures, evaluation of restoration and revitalisation (refunctioning) and the changes in the protected areas of region are discussed with the various suggestions. With the framework of the sustainability of the industrial heritage, the protection of the factory buildings, which are densely deployed in the region, is targeted. At the same time, by bringing the structures into force, it is aimed that the local people who worked in the structures which are among the most important employment centres of city in due course of time, can refresh their memories, lay claim to structures and protect the cultural integrity. Splitting the historical factory buildings in Söğüt region into requisite fields at urban fabric and solution suggestions about usage are evaluated. With the idea of keeping the region alive with these structures by approaching holistically, revitalisation is aimed on this study.